Coexistence of species in exactly solvable multi-species models / Muhammad Saleem … [et al.] - Saleem, Muhammad; H. Sadiyalb, Anuar; Avovaa Saleem, Prithvi Raj; Sapuana Saleem, S.M. (URDC,Universiti Teknologi MARA, Perlis & University Publication Centre (UPENA), 2006)
We consider in this paper some multi-species predator-prey type models with interactions of Gompertz form. These models concern two competing prey species in interaction with one or two predators and three species interactions where one species acts both as a prey and predator. The noticeable feature of these models is that all the models are exactly solvable and hence their solutions are exact and in analytical form, from where all the results contained in the models can be read out directly.